2006
DOI: 10.1152/ajpgi.00074.2006
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of the α-subunit of gustducin with PYY and GLP-1 in L cells of human colon

Abstract: In view of the importance of molecular sensing in the function of the gastrointestinal (GI) tract, we assessed whether signal transduction proteins that mediate taste signaling are expressed in cells of the human gut. Here, we demonstrated that the alpha-subunit of the taste-specific G protein gustducin (Galpha(gust)) is expressed prominently in cells of the human colon that also contain chromogranin A, an established marker of endocrine cells. Double-labeling immunofluorescence and staining of serial sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
238
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(254 citation statements)
references
References 58 publications
11
238
2
3
Order By: Relevance
“…And although there is some support for the involvement of TGR5 signalling in L cell stimulation [9], selective and potent non-bile salt TGR5 agonists failed to consistently stimulate L cell secretion (L. Chen, GlaxoSmithKline, Durham, NC, USA, personal communication). Other bile salt-responsive receptors potentially implicated may include one or more of the bitter receptors located on colonic L cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…And although there is some support for the involvement of TGR5 signalling in L cell stimulation [9], selective and potent non-bile salt TGR5 agonists failed to consistently stimulate L cell secretion (L. Chen, GlaxoSmithKline, Durham, NC, USA, personal communication). Other bile salt-responsive receptors potentially implicated may include one or more of the bitter receptors located on colonic L cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…Taste receptors that respond to sweet, bitter and umami stimuli, together with their associated G-proteins have been identified within the GI mucosa co-localized with several gut peptides including ghrelin GLP-1, GIP, and CCK 88,89 . Sweet, umami and bitter-tasting stimuli are detected by members of two GPCR families, the taste 1 receptor (T1R) and taste 2-receptor family (T2R).…”
Section: Taste Receptorsmentioning
confidence: 99%
“…4 In the last decade, several studies have demonstrated the expression of taste receptors and their downstream signaling molecules in the gut, leading to the hypothesis that gastrointestinal taste system may play a role in the gut chemosensitivity. 5,6 In particular, studies in model cell lines 7,8 and a histochemical study 9 have shown that T2R family members are expressed by entero-endocrine cells (EECs), which constitute a first level of integration of the information coming from the lumen. 10 EECs in the gastrointestinal (GI) tract play a crucial role in the control of food intake through several ways.…”
Section: Introductionmentioning
confidence: 99%